Potential pitfalls from meat particles contaminants on cytolgical diagnosis / Siti Nor Rodhiah Rosaidee - Rosaidee, Siti Nor Rodhiah (2015)
Background: Pitfalls resulted from misinterpretation of cytology samples can lead to diagnostic errors with contaminants mimicking the abnormal cells as one of the major factors. Meat particles is an example of food contaminants that can be present in various cytology samples. The aims of this study are to elucidate the basic cytomorphological structure of meat particles contaminants and compare with normal cells, malignant cells and microorganisms. Methods: Random meat particles were selected. For chicken meat and seafood, scraped cells smeared on slides by using tongue depressor spatula were used. Whereas, catfish was cut into small pieces and directly smeared using 'pick and smear' method. Two smears were prepared, then stained with Papanicolaou stain and May-Grunwald Giemsa stain. Results: Chicken meats mimicked Actinomyces species, cockles resemble with parabasal cells, endocervical and macrophage, short neck clams similar with parabasal cells, shrimp mimicked atypical glandular cells, squid resemble with tumor diathesis and catfish look-like parakeratosis. Conclusion: Cytomorphological of meat particles can resemble normal cells, malignant cells and microorganisms that may contribute to cytodiagnostic error. These finding provides cytomorphological catalogue of meat particles that can be useful in minimizing pitfalls in cytology.